(untitled) (Docentes 2.0 Journal, 2024)
The Andean zone of Peru has many plants that have forage (straw) that is used to feed animals and to make adobes in homes. Its objective was to determine the compressive and flexural resistance of concrete with river sand and Peruvian Andean straw. The research was based on the hypothetical-deductive method, positivist paradigm with a quantitative approach, experimental design and descriptive type. The population and sample were 42 concrete specimens. Its results in the mix design is 1: 1.8: 2 and 19.1 liters of water. Its compressive strength of the standard sample was 155.9 kg/cm2 at 7 days, 218.3 kg/cm2 at 14 days, 222.7 kg/cm2 at 28 days, and the sample with 0.5% plant fiber is 179.8. kg/cm2 at 7 days, 171.3 kg/cm2 at 14 days, 206.7 kg/cm2 at 28 days, in the flexural strength of the standard sample is 27.8 kg/cm2 at 7 days, 27.6 kg/ cm2 at 14 days and 30.2 kg/cm2 at 28 days, the sample with 0.5% plant fiber is 29.7 kg/cm2 at 7 days, 26.6 kg/cm2 at 14 days and 28.1 kg/cm2 at 28 days day.